O012 Cardiovascular risk in a sleep clinic population with Obstructive Sleep Apnoea and association with symptom and polysomnographic profiles. (9th November 2022) - Kemp, E; Sutherland, K; Bin, Y; Chan, A; Dissanayake, H; Yee, B; Kairaitis, K; Wheatley, J; De Chazal, P; Piper, A; Sarkissian, N; Cistulli, P
Abstract: Background: Recent population level data has identified specific symptom and polysomnographic profiles associated with development of cardiovascular disease (CVD) in obstructive sleep apnoea (OSA). Our aims were to determine whether these profiles were present at diagnosis of OSA in pre-existing CVD and high cardiovascular risk. Methods: Participants in the Sydney Sleep Biobank (SSB) database, aged 30-74 years, self-reported presence of CVD (coronary artery disease, cerebrovascular disease, or heart failure). In those without CVD, the Framingham Risk Score (FRS) was calculated to estimate 10-year absolute CVD risk, categorised as "low" (<10%), "intermediate" (10-20%), or "high" (>20%). Groups were compared on symptom and polysomnographic variables. Progress to Date: 629 patients (68% male; mean age 54.3 years (SD 11.6); mean BMI 32.3 (SD 8.2)) were included. CVD was reported in 12.2%. Of the remainder, 27.7% had a low risk FRS, 25.4% had intermediate risk and 34.7% had high risk. Insomnia symptoms of waking too early and difficulty maintaining sleep were more prevalent in the high FRS group (p=0.003 and p=0.05, respectively). CVD and FRS groups differed on multiple polysomnographic variables, however none of these differences remained significant after adjusting for age, sex, and BMI. Intended Outcome and Impact: CVD and high CVD risk are associated with OSA on insomnia symptoms and multiple polysomnographic variables, however these associations are most likely due to demographic differences. Our research adds to the growing body of evidence elucidating the association between OSA and CVD. Further research is needed to translate to personalised management strategies.